Assessment of the exposure of Spanish children and adolescents to bisphenols and parabens using dietary and human biomonitoring data - Patricia González-Palacios; Moustapha Sy; Thomas Tietz; Claudia Lorenz; Ralph Pirow; Vega Almazán-Fernández de Bobadilla; Ana Rivas; Alberto Zafra-Gómez (Environmental Pollution, 2026)

Mono-n-hexyl phthalate: exposure estimation and assessment of health risks based on levels found in human urine samples - Ralph Pirow; Ulrike Bernauer; Annegret Blume; Adrian Cieszynski; Gabriele Flingelli; Astrid Heiland; Matthias Herzler; Bettina Huhse; Christian Riebeling; Esther Rosenthal; Moustapha Sy; Thomas Tietz; et al. (Archives of Toxicology, 2024)
Mono-n-hexyl phthalate (MnHexP) is a primary metabolite of di-n-hexyl phthalate (DnHexP) and other mixed side-chain phthalates that was recently detected in urine samples from adults and children in Germany. DnHexP is classified as toxic for reproduction category 1B in Annex VI of Regulation (EC) 1272/2008 and listed in Annex XIV of the European chemical legislation REACH; thereby, its use requires an authorisation. Health-based guidance values for DnHexP are lacking and a full-scale risk assessment has not been carried out under REACH. The detection of MnHexP in urine samples raises questions about the sources of exposure and concerns of consumer safety. Here, we propose the calculation of a provisional oral tolerable daily intake value (TDI) of 63 µg/kg body weight/day for DnHexP and compare it to intake levels corresponding to levels of MnHexP found in urine. The resulting mean intake levels correspond to less than 0.2% of the TDI, and maximum levels to less than 5%. The TDI was derived by means of an approximate probabilistic analysis using the credible interval from benchmark dose modelling of published ex vivo data on reduced foetal testosterone production in rats. Thus, for the dose associated to a 20% reduction in testosterone production, a lower and upper credible interval of 14.9 and 30.0 mg/kg bw/day, respectively, was used. This is considered a conservative approach, since apical developmental endpoints (e.g. changed anogenital distance) were only observed at higher doses. In addition, we modelled various scenarios of the exposure to the precursor substance DnHexP from different consumer products, taking measured contamination levels into account, and estimated systemic exposure doses. Of the modelled scenarios including the application of sunscreen (as a lotion or pump spray), the use of lip balm, and the wearing of plastic sandals, and considering conservative assumptions, the use of DnHexP-contaminated sunscreen was highlighted as a major contributing factor. A hypothetical calculation using conservative assumptions for the latter resulted in a margin of safety in relation to the lower credible interval of 3267 and 1007 for adults and young children, respectively. Most importantly, it was found that only a fraction of the TDI is reached in all studied exposure scenarios. Thus, with regard to the reported DnHexP exposure, a health risk can be considered very unlikely.

Evidence for an accumulation of mineral oil saturated hydrocarbons (MOSH) in human tissues: a re-evaluation of biopsy and autopsy data - Ralph Pirow; Nicole Concin; Koni Grob (Journal of Consumer Protection and Food Safety, 2024)
Consumers are exposed to mineral oil hydrocarbons (MOH) e.g. through foodstuffs and cosmetics. Upon ingestion, MOH follow the absorption pathway of dietary lipids. Analytical chemistry has revealed the presence of the main fraction, designated as mineral oil saturated hydrocarbons (MOSH), in mesenteric lymph nodes (MLNs), liver, spleen, and adipose tissue. Recent results from animal studies raised concerns about a long-term, possibly irreversible accumulation of some MOSH in humans. To address this issue, we performed a statistical re-analysis of published biopsy and autopsy data regarding the age-dependence of MOSH levels in human tissue. MOSH concentrations in MLNs and adipose tissue showed a 1.2–1.4-fold increase per decade, pointing to very long-term accumulation in both tissues. There was no evidence for age-dependent MOSH concentrations in liver and spleen. There was no sex difference in the MOSH concentrations in MLNs, suggesting a similar oral exposure for men and women. On average, women had a 2.2–2.5-fold higher MOSH concentration in the liver, spleen and adipose tissue compared to men. This finding may point to a sex difference in metabolism, in line with animal data. The use of certain cosmetics was a relevant predictor in addition to age. Women that used cosmetics like lipstick, hand cream, and sun cream had an average 2.1-fold higher MOSH concentration in abdominal subcutaneous fat than non-users.

Physiologically based modelling of dermal absorption and kinetics of consumer-relevant chemicals: A case study with exposure to bisphenol A from thermal paper - Barbara Wiśniowska; Susanne Linke; Sebastian Polak; Zofia Bielecka; Andreas Luch; Ralph Pirow (Toxicology and Applied Pharmacology, 2023)

Reply to the opinion paper “The EU chemicals strategy for sustainability: an opportunity to develop new approaches for hazard assessment” by Scholz et al. - Matthias Herzler; Philip Marx-Stoelting; Ralph Pirow; Christian Riebeling; Andreas Luch; Tewes Tralau; Tanja Schwerdtle; Andreas Hensel (Archives of Toxicology, 2022)

The “EU chemicals strategy for sustainability” questions regulatory toxicology as we know it: is it all rooted in sound scientific evidence? - Matthias Herzler; Philip Marx-Stoelting; Ralph Pirow; Christian Riebeling; Andreas Luch; Tewes Tralau; Tanja Schwerdtle; Andreas Hensel (Archives of Toxicology, 2021)

A scientific review of colorful textiles - Suna Nicolai; Tewes Tralau; Andreas Luch; Ralph Pirow (Journal of Consumer Protection and Food Safety, 2021)
Textiles, especially apparel, play an essential role in our daily life. Given that nearly everybody is in contact with clothes and other textiles 24 h a day, they have to be safe. Today’s manufacturing processes depend on the use of many different chemicals, including dyes. An ideal dye would stay within the fabric during use. However, most textile dyes are prone to leaching and wear-off. Ideally, the industry is trying to keep the respective release of dyestuffs as low as possible. Concomitantly, toxicological risk assessment has to evaluate whether the released amounts are safe based on the substance-inherent characteristics and expected levels of exposure. So far, assessments of the latter are mostly based on what little data is available. Although the use of worst-case scenarios makes systematic overestimation likely and thus warrants a sufficiently high level of consumer protection, existing data gaps should be filled in order to end this unsatisfactory situation. Hence, in a first step this paper compiles and analyzes available data on the migration of dyes from textile materials, dermal dye uptake, and possible reductive cleavage of azo dyes by the skin microbiome as well as the dermal uptake of the resulting cleavage products.

Aggregated aluminium exposure: risk assessment for the general population - Thomas Tietz; Ariane Lenzner; Anna Elena Kolbaum; Sebastian Zellmer; Christian Riebeling; Rainer Gürtler; Christian Jung; Oliver Kappenstein; Jutta Tentschert; Michael Giulbudagian; Stefan Merkel; Ralph Pirow; et al. (Archives of Toxicology, 2019)
Aluminium is one of the most abundant elements in earth’s crust and its manifold uses result in an exposure of the population from many sources. Developmental toxicity, effects on the urinary tract and neurotoxicity are known effects of aluminium and its compounds. Here, we assessed the health risks resulting from total consumer exposure towards aluminium and various aluminium compounds, including contributions from foodstuffs, food additives, food contact materials (FCM), and cosmetic products. For the estimation of aluminium contents in foodstuff, data from the German “Pilot-Total-Diet-Study” were used, which was conducted as part of the European TDS-Exposure project. These were combined with consumption data from the German National Consumption Survey II to yield aluminium exposure via food for adults. It was found that the average weekly aluminium exposure resulting from food intake amounts to approx. 50% of the tolerable weekly intake (TWI) of 1 mg/kg body weight (bw)/week, derived by the European Food Safety Authority (EFSA). For children, data from the French “Infant Total Diet Study” and the “Second French Total Diet Study” were used to estimate aluminium exposure via food. As a result, the TWI can be exhausted or slightly exceeded—particularly for infants who are not exclusively breastfed and young children relying on specially adapted diets (e.g. soy-based, lactose free, hypoallergenic). When taking into account the overall aluminium exposure from foods, cosmetic products (cosmetics), pharmaceuticals and FCM from uncoated aluminium, a significant exceedance of the EFSA-derived TWI and even the PTWI of 2 mg/kg bw/week, derived by the Joint FAO/WHO Expert Committee on Food Additives, may occur. Specifically, high exposure levels were found for adolescents aged 11–14 years. Although exposure data were collected with special regard to the German population, it is also representative for European and comparable to international consumers. From a toxicological point of view, regular exceedance of the lifetime tolerable aluminium intake (TWI/PTWI) is undesirable, since this results in an increased risk for health impairments. Consequently, recommendations on how to reduce overall aluminium exposure are given.

Characterization of chemical-induced sterile inflammation in vitro: application of the model compound ketoconazole in a human hepatic co-culture system - Franziska Wewering; Florent Jouy; Dirk K. Wissenbach; Scarlett Gebauer; Matthias Blüher; Rolf Gebhardt; Ralph Pirow; Martin von Bergen; Stefan Kalkhof; Andreas Luch; Sebastian Zellmer (Archives of Toxicology, 2017)

Regulatory toxicology in the twenty-first century: challenges, perspectives and possible solutions - Tewes Tralau; Michael Oelgeschläger; Rainer Gürtler; Gerhard Heinemeyer; Matthias Herzler; Thomas Höfer; Heike Itter; Thomas Kuhl; Nikola Lange; Nicole Lorenz; Christine Müller-Graf; Ulrike Pabel; et al. (Archives of Toxicology, 2015)

Safety limits for elements in toys: a comparison between the old and the new European toys safety directive - Bärbel Vieth; Ralph Pirow; Andreas Luch (Archives of Toxicology, 2014)

Seasonal and interannual changes in water temperature affect the genetic structure of a Daphnia assemblage ( D. longispina complex) through genotype‐specific thermal tolerances - Rüdiger J. Paul; Ansgar Mertenskötter; Olaf Pinkhaus; Ralph Pirow; Ulrike Gigengack; Ina Buchen; Marita Koch; Wolfgang Horn; Bettina Zeis (Limnology and Oceanography, 2012)
A field and laboratory study was carried out over 3 yr to determine relationships between seasonal and interannual changes in temperature (year‐specific temperature courses, presence or absence of ice in winter) and the genetic structure (composition of multilocus genotypes [MLGs]) of a Daphnia longispina assemblage. Field studies on temperature and genetic structures were linked with laboratory analyses to evaluate the thermal tolerance of long‐term 12°C‐, 18°C‐, and 24°C‐acclimated clonal lineages (CLs) derived from abundant MLGs sampled in the field (surface water and thermocline). The tolerance to warm temperatures (heat tolerance) was lowest in CLs derived from MLGs that were dominant directly after or before winter (winter‐CLs), higher in “spring‐autumn‐CLs,” and highest in “summer‐CLs.” Winter‐CLs also showed the highest degree of physiological plasticity. The differences in heat tolerance were mainly related to the different genotypes of the phosphoglucomutase ( PGM ) locus. Temperature conditions during winter and early spring affected the heat tolerance of all CLs as well as the success of different winter survival strategies (overwintering, resting eggs). Heat tolerance was lowest in CLs derived from MLGs sampled in 2006 (after the coldest winter and spring period), higher in CLs from 2005 (after a less cold winter and spring period), and highest in CLs from 2007 (after a warm, ice‐free winter). In addition to other environmental factors (predation, parasitism, food), seasonal and interannual changes in temperature affect Daphnia genetic structure through genetic differences in thermal responses, thermal tolerance, and physiological plasticity.

Developmental toxicity testing in the 21st century: the sword of Damocles shattered by embryonic stem cell assays? - Andrea Seiler; Michael Oelgeschläger; Manfred Liebsch; Ralph Pirow; Christian Riebeling; Tewes Tralau; Andreas Luch (Archives of Toxicology, 2011)

Estrogen and Progestogen Correlates of the Structure of Female Copulation Calls in Semi-Free-Ranging Barbary Macaques (Macaca sylvanus) - Dana Pfefferle; Michael Heistermann; Ralph Pirow; J. Keith Hodges; Julia Fischer (International Journal of Primatology, 2011)

Alternatives to animal testing: current status and future perspectives - Manfred Liebsch; Barbara Grune; Andrea Seiler; Daniel Butzke; Michael Oelgeschläger; Ralph Pirow; Sarah Adler; Christian Riebeling; Andreas Luch (Archives of Toxicology, 2011)

Cationic composition and acid–base state of the extracellular fluid, and specific buffer value of hemoglobin from the branchiopod crustacean Triops cancriformis - Ralph Pirow; Ina Buchen; Marc Richter; Carsten Allmer; Frank Nunes; Andreas Günsel; Wiebke Heikens; Tobias Lamkemeyer; Björn M. von Reumont; Stefan K. Hetz (Journal of Comparative Physiology B, 2009)